Short-term maraviroc exposure, a clinical approach to decide on maraviroc prescription in HIV-1-infected treatment-naïve patients - Gonzalez-Serna A; Genebat M; Ruiz-Mateos E; Leal M (Dove Medical Press, 2016)
Alejandro Gonzalez-Serna,1 Miguel Genebat,2 Ezequiel Ruiz-Mateos,2 Manuel Leal2 1Laboratory of Molecular Immunobiology, Hospital General Universitario Gregorio Maranon, Madrid, 2Laboratory of Immunovirology, Institute of Biomedicine of Seville, Seville, SpainWoollard and Kanmogne1 have generated an exhaustive review on maraviroc and its use in human immunodeficiency virus (HIV) infection. Within their interesting dissertation, they discuss about the maraviroc clinical test (MCT), a clinical approach developed in our group in order to decide candidate patients to receive maraviroc as part of a further combined antiretroviral therapy, as an alternative to genotypic and phenotypic tropism assays.2View the original article by Woollard and Kanmogne